Understanding STEM teacher learning in an informal setting: a case study of a novice STEM teacher - Mi Song Kim; Najmeh Keyhani (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract Research into informal STEM education over the past years has shown that informal learning environments increase students' learning in STEM. However, how STEM teachers learn in an informal setting remains unclear. Such educators who work in informal settings are not all required to have undergone teacher education or professional development, and their progress may differ from other teachers' experiences. As a result, it is important to observe and understand the path such teachers take to see how they develop their teacher identities. Drawing upon Baxter Magolda's (Making their own way: Narratives for transforming higher education to promote self-development, 2004) self-authorship framework, this qualitative case study explores the progress of one informal STEM teacher throughout her first class by qualitatively analyzing her journals, lesson plans, and artifacts. The teacher's journey progresses towards self-authorship in a nonlinear way with multiple signs of the epistemological, intrapersonal, and interpersonal dimensions of the framework being deeply interconnected to one another. Implications for STEM teacher education within the context of informal STEM education are discussed.